The Concept of Aging in Buddhist Philosophy: A Path to Wisdom and Liberation - Chau, Troung Minh (BUDDHO, 2024)
Aging is a universal and inevitable process, yet its perception and experience vary across cultures and philosophical traditions. This study explores Buddhist perspectives on aging, emphasizing the concepts of impermanence (anicca), suffering (dukkha), non-self (anatta), mindfulness, ethical living, and spiritual liberation. Buddhism presents aging not as a decline but as a phase of profound spiritual significance, offering individuals the opportunity to cultivate wisdom (paññā) and deepen their practice of meditation. The study highlights how the Buddhist understanding of impermanence fosters acceptance of aging as a natural transition, reducing suffering by detaching from worldly concerns. Furthermore, the principle of non-self challenges rigid attachments to identity, enabling aging individuals to transcend ego-driven fears and embrace change with equanimity. Mindfulness and meditation emerge as essential tools for aging gracefully, with empirical research supporting their benefits in reducing stress, enhancing cognitive function, and fostering emotional resilience. Ethical living and compassion (mettā) also play a critical role, as Buddhist teachings encourage social support and interconnectedness, reinforcing the importance of kindness and communal care in later life. Ultimately, aging is framed as an opportunity for spiritual liberation (vimutti), with the later stages of life providing an ideal time for moral cultivation and preparation for enlightenment (nibbāna). The findings contribute to the broader discourse on aging by offering an alternative framework that prioritizes wisdom, detachment, and spiritual fulfillment over physical decline. This perspective challenges dominant Western narratives of aging, providing a holistic approach that integrates psychological well-being with ethical and spiritual growth. The study underscores the relevance of Buddhist teachings in contemporary discussions on aging, mental health, and human development, highlighting their potential applications in both personal and institutional contexts.